PENERAPAN MODEL PROBLEM SOLVING BERBANTUAN GEOGEBRA DALAM PEMBELAJARAN MATEMATIKA PADA MATERI TRANSLASI - Hasra Daud Mangamis (Afore : Jurnal Pendidikan Matematika, 2026)
This study aims to analyze the effect of applying the Problem Solving learning model assisted by GeoGebra on students’ mathematics learning outcomes, specifically in the topic of translation. The research employed a quasi-experimental approach using a pretest–posttest control group design involving two ninth-grade classes at SMP Negeri 3 Tondano with a total of 27 students. The experimental class received learning through the Problem Solving approach integrated with GeoGebra, while the control class was taught using conventional methods. The research instrument consisted of a five-item essay test designed to measure students’ understanding of translation concepts. Data analysis included normality and homogeneity tests to ensure that both groups met the statistical assumptions required for further analysis, followed by an independent t-test to determine differences in learning outcomes. The results show that the experimental group achieved a higher posttest mean score of 90.77, whereas the control group obtained a mean score of 66.43. The independent t-test produced tcount = 12.26, which was greater than ttable = 1.70 at a 0.05 significance level. These findings indicate that the use of the Problem Solving model assisted by GeoGebra significantly improves students’ mathematics learning outcomes. The integration of GeoGebra helps students visualize translation concepts more effectively, thereby enhancing comprehension and supporting problem-solving skills.